2021
DOI: 10.3389/fmolb.2021.614443
|View full text |Cite
|
Sign up to set email alerts
|

Non-RBM Mutations Impaired SARS-CoV-2 Spike Protein Regulated to the ACE2 Receptor Based on Molecular Dynamic Simulation

Abstract: The emergence of novel coronavirus mutants is a main factor behind the deterioration of the epidemic situation. Further studies into the pathogenicity of these mutants are thus urgently needed. Binding of the spinous protein receptor binding domain (RBD) of SARS-CoV-2 to the angiotensin-converting enzyme 2 (ACE2) receptor was shown to initiate coronavirus entry into host cells and lead to their infection. The receptor-binding motif (RBM, 438–506) is a region that directly interacts with ACE2 receptor in the RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After searching for variants and verifying by Sanger sequencing in the BLAST dataset, we found that compared to normal gene sequences, there were multiple variants in the PICK1 gene in patients with azoospermia, most of which are single nucleotide variants (SNVs). Therefore, we speculate that the PICK1 gene is involved in the occurrence and development of azoospermia, and its variants are part of the gene weakening of sperm motility, by integrating the genetic model and molecular dynamic simulation methods in our recent study [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…After searching for variants and verifying by Sanger sequencing in the BLAST dataset, we found that compared to normal gene sequences, there were multiple variants in the PICK1 gene in patients with azoospermia, most of which are single nucleotide variants (SNVs). Therefore, we speculate that the PICK1 gene is involved in the occurrence and development of azoospermia, and its variants are part of the gene weakening of sperm motility, by integrating the genetic model and molecular dynamic simulation methods in our recent study [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, many functions of biological macromolecular systems are difficult to realize without the contribution of entropy effects, such as the shape entropy in the structural organization of many protein macromolecules with shape anisotropy, the conformational entropy on which the realization of the function of an intrinsically disordered protein depends, and entropy in thermodynamics of the liquid–liquid phase separation of living macromolecular systems. 76–79 It has been recognized that the chain stiffness or flexibility of active macromolecules can be harnessed to tune the entropy–enthalpy balance, which is also identified in biological macromolecular systems. For example, recent research has shown that, with the increase of the DNA chain length, the conformational entropy of chains plays a more important role in the structural organization, and can even determine the type of superlattice structures.…”
Section: Applications Of the Entropy-controlled Strategy By Confinementmentioning
confidence: 99%
“…This would lead the RBD-ACE2 binding affinity of the Alpha variant and the Delta variant with ACE2 to be obviously bigger than that of the original SARS-CoV-2. Although the RBD mutation at amino-acid position 498 is not a missense mutation that presented in one or more of the VOCs, the RBD mutation such as Q498A has also been reported [51][52][53]. At the interface of a protein-protein complex, interactions among the surface areas of proteins can be classified into four types: hydrophobic-hydrophobic (Ho-Ho) interaction, hydrophobic-hydrophilic (Ho-Hi) interaction, attractive dipole-dipole (ADD) interaction, and repulsive dipole-dipole (RDD) interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This would lead the RBD-ACE2 binding affinity of the Alpha variant and the Delta variant with ACE2 to be obviously bigger than that of the original SARS-CoV-2. Although the RBD mutation at amino-acid position 498 is not a missense mutation that presented in one or more of the VOCs, the RBD mutation such as Q498A has also been reported [51][52][53].…”
Section: Introductionmentioning
confidence: 99%